Recombinant infectious bronchitis coronavirus H120 with the spike protein S1 gene of the nephropathogenic IBYZ strain remains attenuated but induces protective immunity. Issue 15 (30th March 2020) - Jiang, Yi; Cheng, Xu; Zhao, Xiumei; Yu, Yan; Gao, Mingyan; Zhou, Sheng
Highlights: The reverse genetic operating systems of IBV H120 and IBYZ strains were created. We constructed rH120-S1/YZ strain, based on the backbone of the H120 vaccine strain, with the S1 gene replaced with that of the QX-like nephropathogenic strain, ck/CH/IBYZ/2011. We demonstrated that rH120-S1/YZ had the potential to be a candidate vaccine strain for the prevention and control of the epidemic of renal strains. Abstract: Infectious bronchitis (IB) is a highly infectious viral disease responsible for major economic losses in the poultry industry. A reverse genetic vaccine is a safe, rapid, and effective method of achieving IB prevention and control. In this study, we constructed the recombinant strain, rH120-S1/YZ, using a reverse genetic system, based on the backbone of the H120 vaccine strain, with the S1 gene replaced with that of the QX-like nephropathogenic strain, ck/CH/IBYZ/2011, isolated in China. The results of dwarf chicken embryos, growth kinetics, and viral titration in the embryos demonstrated that the biological characteristics of the recombinant virus remained unchanged. Like the rH120-infected group and in contrast to the rIBYZ-infected group, no mortality, clinical signs, or lesions were observed in the lungs or kidneys of young chickens inoculated with rH120-S1/YZ. The viral loads in various tissues, cloacal, and oral swabs was lower in most types of samples, indicating that the rH120-S1/YZ strain was highly safe in chicks. Compared to rH120 vaccination group, when the efficacy of this strain was evaluated against the QX-like IBV strain, better protection, with 100% survival rate and no disease symptom or gross lesion was observed in the chickens vaccinated with rH120-S1/YZ. Increased levels of IBV-specific antibodies were detected in the serum of the rH120-S1/YZ-vaccinated animals 14 days post-vaccination. Collectively, our results suggest that the recombinant strain, rH120-S1/YZ, may represent a promising vaccine candidate against QX-like IBVs.